Effects of positional variables on shooting outcome in elite football - Schulze, E.; Mendes, B.; Mauricio, N.; Furtado, B.; Cesario, N.; Carrico, S.; Meyer, T. (Science and Medicine in Football, 2018)
Objective: To analyse shooting situations in elite football (soccer) by incorporating opponent positioning for shots from the same location. Methods: All attempts by foot during four seasons (2011-2012 until 2014-2015) of an elite team's home matches were analysed. Three locations with the highest density of shots (n = 21, 24, and 20) were identified and selected. The positioning of defenders (closest, first and number of opponents in line to the goal) and the goalkeeper was determined and analysed for the outcome of each shot (being a goal, on arget, or based on placement). Results: For shots from a tight angle, the distance of the closest defender correlated with improved shot placement (r = -0.39, P = 0.04). For shots from a close range, the sight of goal affected shots going on or off target (ES = 0.77, P = 0.03). Finally, for shots from a longer range, none of the positional variables correlated with shot outcome. Conclusions: Adding context to shooting performance, by taking opponent positions into account, increased the amount of relevant information for the analysis of shooting performance. Since different variables were found to relate to the outcome of shots from different positions, the significance of contextualising match events has been highlighted.